2020
DOI: 10.1016/j.fertnstert.2020.08.546
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Route of Progesterone Administration on Outcomes of Pregnancies Affected by Subchorionic Hematoma Following Frozen Ivf Cycles

Abstract: OBJECTIVE: Chronic endometritis (CE) has been associated with recurrent pregnancy loss (RPL) and recurrent implantation failure. Incidence rates vary due to significant heterogeneity in biopsy timing and diagnostic criteria. Our group previously demonstrated that plasma cells are found in 59% of endometrial biopsies (EMBs) in the follicular phase compared to 18% in the luteal phase, which led us to question whether menstruation or hormonal changes in the follicular phase impact the diagnosis of CE. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…47 It has been hypothesized that progesterone therapy in the pregnancies complicated by first trimester SCH may decrease later complications, to include preterm premature rupture of membranes and fetal loss; however, this has not been proven to be effective at this time. 48 During frozen embryo transfer cycles, a retrospective cohort study by Miranian et al 48 demonstrated that the use of intramuscular versus vaginal progesterone significantly reduced the incidence of SCH (23.9% vs 0.4%); however, the investigators found no difference in first or second trimester losses or live birth rates.…”
Section: Management and Investigational Or Theoretical Treatmentmentioning
confidence: 99%
“…47 It has been hypothesized that progesterone therapy in the pregnancies complicated by first trimester SCH may decrease later complications, to include preterm premature rupture of membranes and fetal loss; however, this has not been proven to be effective at this time. 48 During frozen embryo transfer cycles, a retrospective cohort study by Miranian et al 48 demonstrated that the use of intramuscular versus vaginal progesterone significantly reduced the incidence of SCH (23.9% vs 0.4%); however, the investigators found no difference in first or second trimester losses or live birth rates.…”
Section: Management and Investigational Or Theoretical Treatmentmentioning
confidence: 99%